PERLINDUNGAN HUKUM TERHADAP PENGUASAAN HARTA BAWAAN DAN HARTA BERSAMA SETELAH PERCERAIAN MENURUT UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN BERBASIS KEADILAN - Zulfiani Zulfiani (UNISSULA, 2015)
In marriage institutions the community has long known the mixing of marriage property. Both joint property and possessions. The arrangement of joint property and luggage is regulated in Chapter VII Article 35 paragraph (1) and (2) of Law No. 1 of 1974 on Marriage. Control over joint property after divorce is divided into two / seperdua while the property is controlled by each party. And for the legal protection of marital property, a marriage contract (Prenuptial Agreement) is applied for the religious observers in the Office of Religious Affairs in the presence of the Registrar Officer, while the Non-Muslim Officers are conducted at the Civil Registry to anticipate the legal consequences of the property in marriage.